Improving preoperative management of women with high-grade cervical intraepithelial neoplasia - Volkov V.G; T.V. Zakharova (LCC «Medicine-Inform», 2019)
V.G. Volkov1, T.V. Zakharova2 1Tula State University, Tula, Russian Federation 2E.G. Lazarev Tula City Clinical Hospital No. 2, Tula, Russian Federation Background: persistent infection with oncogenic subtypes of human papillomavirus is the major cause of cervical cancer. Correlation between bacterial vaginosis and virus persistence in squamous cervical epithelium was revealed. Aim: to study the efficacy of preoperative Gaynomax for isolated bacterial vaginosis or in combination with genital candidiasis in women with high-grade cervical intraepithelial neoplasia (CIN). Patients and Methods: complex clinical microbiological study and treatment were performed in 25 women aged 24-58 years (36.9±3.6 years). High-grade CIN was diagnosed in a total of 25 women. Gaynomax was prescribed preoperatively, i.e., before large loop excision biopsy (1 vaginal suppository twice a day for 3 days). Results: at the first visit, 12 women (48%) have reported on the complaints, 5 women (20%) reported on the complaints after active questioning only, 8 women did not reported any urogenital complaints. High  risk human papillomavirus (subtypes 16, 18, and 33) and bacterial vaginosis (associated with genital candidiasis in 9 women) were identified in a total of 25 women. Gaynomax resulted in clinical laboratory improvement (i.e., itching relief and significant decrease in vaginal discharge amount) in all women. Drug tolerability was good. Adequate wound healing and no postoperative complications were reported after large loop excision biopsy. Conclusion: preoperative Gaynomax for bacterial vaginosis before cervical procedures for high-grade CIN provides great clinical effect confirmed by microbiological study results. Keywords: cervical intraepithelial neoplasia, cervical biopsy, human papillomavirus, bacterial vaginosis, Gaynomax. For citation: Volkov V.G., Zakharova T.V. Improving preoperative management of women with high-grade cervical intraepithelial neoplasia. Russian Journal of Woman and Child Health. 2019;2(3):243-246.